PENGARUH TEKNOLOGI IT PADA MODEL PEMBELAJARAN DISCOVERY CONSTRUCTIVE LEARNING UNTUK MENINGKATKAN PEMAHAMAN SISWA MENGENAI ZAT ADITIF MAKANAN DI KELAS VIII SMP KALAM KUDUS MEDAN - Neva Asih Sary Silalahi; Ida Duma Riris; Marham Sitorus (PROSIDING SEMINAR KIMIA, 2023)
This research aims for knowing is there is difference enhancement results study chemistry SMP Kalam Kudus Medan using flash animation media with Ms. Power Point on the Discovery Constructive Learning model. The population in this study were students class VIII-B and VIII-C SMP Kalam Kudus Medan. Taking sample study taken by purposive sampling consisting of from class learning Discovery Constructive Learning with flash animation media and in class learning Discovery Constructive Learning with Ms. Power Point media. Type this research is research experiment pseudo . Based on the results of the data requirements test , it is known that both the result data study student class learning Discovery Constructive Learning with flash animation media and class Discovery Constructive Learning with Ms. Power Point media is stated is normally distributed and has uniform variance (homogeneous) . Based on the normalized gain data , the increase in results learn using _ learning Discovery Constructive Learning with flash animation media is 84.43% and an increase results learn using _ Discovery Constructive Learning with Ms. Power Point media is 71.06 %. The size difference enhancement results study chemical students is 13.37%. Test results hypothesis , obtained t < -t½α and t > t½α by using t test two party namely 0.0437 < -0.025 and 0.0437 > 0.025 at the level significance = 0.025. This means that H0 is rejected and Ha is accepted , where Ha = exists difference enhancement results study chemistry SMP Kalam Kudus Medan using flash animation media with Ms. Power Point on the Discovery Constructive Learning model for class VIII SMP Kalam Kudus Medan on the subject discussion substance additive food 2013/2014. Keywords: Discovery Constructive Learning model, IT media , SMP Kalam Kudus Medan